The effect of nutrition theraphy on oxidative stress, inflammation, glycemic control in type 2 diabetes patients - Arıtıcı Colak, Gözde; Kiziltan, Gul (Progress in Nutrition, 2019)
Aims: Type 2 diabetes mellitus is a metabolism disease which is seen frequently among adult population in Turkey. The aim of this study was to determine the medical nutrition theraphy effect on oxidative stress, inflammation, glycemic control in type 2 diabetes patients.